Climate change and women’s voice and agency beyond the household: Insights from India - Takeshima, Hiroyuki; Raghunathan, Kalyani; Kosec, Katrina (International Food Policy Research Institute, 2022)
Women’s Voice & Agency beyond the household (VABH) has increasingly been recognized as critical to strengthening resilience, increasing women’s access to important resources, improving women’s decision-making power, and facilitating broader social networks (Njuki et al. 2022). Despite rapidly intensifying climate change in recent years, a knowledge gap persists as to how climate change may affect women’s VABH in developing countries. This has been particularly challenging in countries like India, which host one of the largest numbers of the poor and has been increasingly plagued by droughts, floods, cyclones, rising temperatures, and increasing rainfall fluctuations. This study provides a conceptual discussion on the linkages between climate change and VABH and analyzes their empirical relationship using multiple rounds of nationwide household data from India (India Human Development Survey 2005, 2012; World Values Survey 2001, 2006, 2012); climate data; and data on women’s political representation at the district level. Our results suggest that in rural parts of India, adverse climate change and natural disasters, such as cyclones and/or floods, have consistently negative associations with a broad range of VABH-related outcomes. Moreover, in rural areas, greater political representation by women in district assemblies broadly mitigates the potential effects of adverse climate change on VABH-related outcomes. These patterns generally hold across various populations, differentiated by marriage status and age groups, and are more robust in rural compared to urban areas. There are also generally consistent gender differences in these associations. Specifically, results indicate that women’s VABH are disproportionately more negatively affected by adverse CC than men’s VABH, while greater female representation at local district assemblies has greater effects in mitigating adverse CC on VABH among women than men. The results underscore the importance of enhancing women’s political representation as a means to improve women’s VABH.